Karakteristik CEO dan Pengungkapan Informasi ESG Perusahaan Publik Indonesia - Yapianto, Wilson; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 33 No 12 (2023)DO - 10.24843/EJA.2023.v33.i12.p02, 2023)
This research aims to determine the influence of CEO educational background, CEO tenure and CEO age on ESG information disclosure. This research was conducted on manufacturing sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sample for this research was determined using a purposive sampling method with a sample of 32 observations. The collected data was analyzed using multiple linear regression. The results of the analysis show that the CEO educational background and CEO tenure variables do not have a significant influence on ESG distance, while CEO age has a negative influence on ESG distance. Research can provide information to companies in selecting CEOs with stereotypes by revealing ESG and factors that can influence it, namely the age of the CEO. It can be recommended that companies monitor ESG reporting and disclosure, while still considering the age of a CEO which influences ESG reporting. Keywords: Educational Background; Tenure; Age; ESG